The academic and psychological impact of COVID-19 outbreak on medical students in Sudan - Korashi, Mohamed Magzob (Gezira Journal of Health Sciences, 2021)
Background: The COVID-19 outbreak gave rise to new and unfamiliar challenges upon medical students in Sudan which may have a significant potential to affect their mental and physical well-being. Medical students in Sudan Also encountered an abrupt cutoff from both medical and clinical training since the beginning of the outbreak without implementing a compensatory learning method, which may affect the academic status of medical students in Sudan. Objectives: This study aimed to identify the effect of the COVID-19 outbreak on the psychological and academic status of medical students in Sudan. Methods: This is a prospective descriptive study conducted on undergraduate medical students from three of the top medical schools in the Republic of Sudan, all of which are recognized by the WHO. Data were collected between June and July 2020 using multiple conventional methods on an online-based pre-tested & validated 45 items questionnaire. Data were collected using Microsoft Excel software and all statistical analyses were performed using IBM SPSS statistics software. Results: A total of 357 medical students participated in the study from 3 medical schools in the Republic of Sudan. The participants reported a remarkable negative drop in their mood following the pandemic compared to their mood before it. Social isolation, relatives, or friends getting infected and career uncertainty were the most prominent negative influencers. 85.4% of the participants experienced at least one symptom of anxiety during the outbreak. 56% of the participants experienced panic attacks during the pandemic. 82.6% of the participants experienced at least one symptom of depression. 11.2% of the participants scored a high-risk factor for suicide, 25.5% scored a medium risk while 39.5% scored a low risk. All of the participants reported that they are not getting any form of education from their medical schools during the pandemic. Only 2.5% of the participants are engaged in health care roles. 76.2% reported that they are not studying medicine at the same rate before the shutdown of universities. 59.9% of the participants did not get involved in any medical academic activity during the pandemic. 62.7% did not study any new medical material during the pandemic. 90.6% reported that they did not assess their medical knowledge and clinical skills during the pandemic and 76.8% did not recite medical topics they had in the past. Conclusion: The COVID-19 outbreak in Sudan harms both the psychological well-being and the academic status of medical students. This study reflects the psychological and academic impact of a pandemic on a developing country and its side effects on medical students therefore it’s necessary to conduct further research on the matter to find solutions and prevent future reoccurrence.